Ultrasound Assisted Extraction and Characterization of Bioactives From V Roots to Evaluate Their Antioxidant and Medicinal Potential - Fatima Shahbaz; Naheed Akhter; Muhammad Shahid*; Muhammad Riaz; Fozia Anjum; Fatma Hussain (SAGE Publishing, 2022)
Worldwide, Verbascum thapsus is used for the treatment of various ailments owing to the presence of bioactives of therapeutic potential. Current study was planned to extract bioactives from V thapsus roots using methanol and water as solvents under stimulated effect of ultrasonic waves and characterize them to evaluate their potential benefits. Proximate analysis explored the presence of significant contents of protein, fats, fiber, organic and inorganic minerals. Fourier transform infrared spectra and high-performance liquid chromatography chromatogram indicated the presence of different phytochemicals having antioxidant potential as evidenced by total phenolic contents, total flavonoids content and 2,2-diphenyl-1-picrylhydrazyl activity of both extracts. Both extracts displayed excellent antimicrobial potential against Staphylococcus aureus (S aureus) and Fusarium Solani (F solani) . Aqueous and methanolic extracts exhibited higher inhibition of biofilm made by Bacillus subtilis (B subtilis) as 55.09 and 61.58%, respectively in comparison to biofilm of Escherichia coli ( E coli) as 48.11 and 36.51%, respectively. Methanol extract exhibited anti-amylase activity (IC 50 5.26 ± .31 μg/mL) with an inhibition rate of 68.11% whereas IC 50 of aqueous extract was 6.59 ± .53 μg/mL with an inhibition rate of 63.53%. Inhibitory potential against α-glucosidase (IC 50 3.70 ± .94 ppm) was demonstrated by methanol extract in comparison to aqueous extract (IC 50 7.58 ± .15). The study concluded that V thapsus roots have significant medicinal potential due to the presence of variety of bioactive molecules and can be used in pharmaceutical preparations.